Effects of Spirulina platensis microalgae on antioxidant and anti-inflammatory factors in diabetic rats - Nasirian F (Dove Medical Press, 2018)
Fariba Nasirian,1 Masoumeh Dadkhah,2 Nasrollah Moradi-kor,3,4 Zia Obeidavi5 1Department of Animal Sciences, University of Birjand, Birjand, Iran; 2Research Centers Development and Coordination Office, Deputy of Research & Technology, Ardabil University of Medical Sciences, Ardabil, Iran; 3Research Centre of Physiology, Faculty of Medicine, Semnan University of Medical Sciences, Semnan, Iran; 4Student Research Committee, Faculty of Medicine, Semnan University of Medical Sciences, Semnan, Iran; 5Student Research Committee, Lorestan University of Medical Sciences, Khorramabad, Iran Objectives: Lipid peroxidation and hyperglycemia are common signs for diabetes. Natural antioxidants such as Spirulina platensis microalgae (SPM) may prevent lipid peroxidation and hyperglycemia. This study aimed to evaluate the effects of SPM on antioxidant and anti-inflammatory in diabetic rats. Materials and methods: Sixty-four rats were divided into eight groups (n=8) and orally treated with 0, 10, 20 and 30 mg/kg body weight of SPM extract. Experimental groups included diabetic rats fed with 0 (DC), 10, 20 and 30 mg/kg SPM. Healthy rats were treated with 0 mg/kg SPM (HC), 10 mg/kg SPM, 20 mg/kg SPM and 30 mg/kg SPM. At the end of the trial, blood samples were collected and the plasma concentrations of trace minerals (TMs), biochemical parameters, and antioxidant enzymes in liver were evaluated. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), TNF-α (tumor necrosis factor-alpha) and IL-6 (interleukin-6) were evaluated. Results: Our findings showed that diabetes significantly lowered the plasma concentration of TMs and antioxidant enzymes in liver and also increased the levels of malondialdehyde, glucose, lipid profile, AST, ALT, TNF-α and IL-6 (DC vs HC). However, an oral supplement of SPM (20 and 30 mg/kg body weight) lowered levels of malondialdehyde level, glucose, lipid parameters, AST, ALT, TNF-α and IL-6. The same levels increased the plasma contents of zinc, iron, copper and selenium and activity of antioxidant enzymes (P<0.05). Conclusion: It can be concluded that diabetes decreases TM concentration and antioxidant enzymes and also increases lipid profile, glucose, AST, ALT, TNF-α and IL-6 concentrations. Inclusion of SPM supplementing (20 and 30 mg/kg body weight) increased some TMs and antioxidant enzymes. SPM may provide TMs for synthesis of antioxidant enzymes which subsequently reduce lipid profile, glucose concentration and anti-inflammatory responses. Keywords: antioxidant enzymes, diabetes, lipid profile, plasma selenium, Spirulina platensis